Patient related factors that influence utilization of antenatal care at Saku sub-county, Kenya - Murithi, David; Oluchina, Sherry; Kariuki, Dainah (International Journal Of Community Medicine And Public Health, 2020)
Background: Antenatal care (ANC) is the continuous care that is accorded to women in the course of pregnancy. Notably, antenatal care is an efficient health intervention aimed at inhibiting maternal mortality and morbidity majorly in areas where women have poor health. This study therefore assessed the patient related factors that influence utilization of ANC at Saku sub-county, Kenya. Methods: This research applied descriptive cross sectional study design. The study was carried out in Saku Sub County in the following randomly selected health facilities: Marsabit County Referral Hospital, Dakabaricha Dispensary and Jirime Dispensary. The study population comprised of post-natal mothers aged between 15-49 years seeking services at maternal and child health clinic (MCH) in Saku Sub County. The Cochran's Sample Size Formula was used to calculate a sample size of 154 respondents. The study employed a researcher- administered semi-structured questionnaire and use of focused group discusions. Descriptive statistics, chi-square tests and logistic regression were used in the analysis. Results: Tertially/University education was significantly associated with utilization of ANC Services (OR=0.377, p-value=0.012, 0.177-0.806). There was a significant association between. The age between 15-19 years with the utilization of ANC services (OR =2.470, p-value=0.044, 1.024-5.955). Conclusions: There was a significant association between utilization of Antenatal care and receiving support from family members (p-value=0.035). Mothers are likely to utilize ANC services more often if they receive family support. Therefore, family support exerts a positive impact on a pregnant woman’s psychological well-being, as well as on the health of her newborn. Sensitizing men about antenatal services and their benefits health-care providers is important.